How Perceived Value Mediates Muslim Consumer Loyalty to Halal Cosmetics: An Analysis of Labelling, Price, and Quality - Sholeh, Khabib; Afif Zaerofi; Yono Haryono (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Community productivity is critical in maintaining quality of life to avoid disasters. The use of digital technology in the economic aspect has also provided opportunities for people far from the market to earn income to meet their living needs. Objective: This quantitative study aimed to explore the impact of halal labeling, price, and product quality on consumer loyalty toward Indonesian skincare products among Muslim consumers in the Jabodetabek area. Specifically, it examines the mediating role of perceived value in these relationships. Method: Primary data were collected through a questionnaire distributed to 115 Muslim respondents who used Indonesian skincare products from Jabodetabek. The study employed random sampling was used for the participant selection. For data analysis, Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was used to assess both the direct and indirect effects of the variables. Result: This finding revealed that labeling and price do not directly affect consumer loyalty. At the same time, product quality and perceived value do, with the latter being positively influenced by price and product quality. The study also concludes that perceived value is a crucial driver of consumer loyalty, emphasizing that companies should focus on enhancing product quality and perceived value to strengthen consumer loyalty while recognizing that halal labeling, although important in principle, does not directly impact consumer loyalty or perceived value. Implication: The findings suggest that product quality and perceived value are critical drivers of consumer loyalty for skincare products targeting Muslim consumers in Jabodetabeky. Halal labeling, while necessary in principle, does not directly influence loyalty or perceived value. Companies should prioritize enhancing product quality and delivering perceived value to strengthen consumer loyalty while considering competitive pricing strategies that enhance perceived value.